Further Understanding about the Mechanism of Vitamin D on Blood Pressure - Farapti Farapti; Chusnul Fadilla (Universitas Gadjah Mada, 2021)
Globally, the prevalence of vitamin D deficiency and hypertension is both increasing. Various studies have also identified that both are likely to have causality relationships. The mechanisms and possibilities of such relationships will be discussed in this article. This literature study takes systematic review and meta-analysis research as well as randomly other research to complete the discussion on the role, effects, and mechanisms of vitamin D to blood pressure. Vitamin D is a fat-soluble vitamin that can be produced by the body and the most proper measurement using 25(OH)D. Low vitamin D is one of the risk factors for increased blood pressure (BP). Administration of vitamin D seems beneficial to lowering BP through various mechanisms including inhibit renin gene expression, maintain PTH levels and calcium homeostasis, vasodilatation BP, and decrease sympathetic nerve activity. Research with vitamin D supplementation reported random data between effective and whether or not to decrease BP. Vitamin D can be significantly beneficial in only some conditions although overall it has increased levels of 25(OH)D. However, although vitamin D is very good for health improvement, the use of vitamin D specifically as an antihypertensive still needs more understanding and research on the conditions that have proven effective in their use.